Brief reasons for living inventory: a psychometric investigation - Jan Christopher Cwik; Paula Siegmann; Ulrike Willutzki; Peter Nyhuis; Marcus Wolter; Thomas Forkmann; Heide Glaesmer; Tobias Teismann (BMC Psychiatry, 2017)
Abstract Background The present study aimed at validating the German version of the Brief Reasons for Living inventory (BRFL). Methods Validity and reliability were established in a community (n = 339) and a clinical sample (n = 272). Convergent and discriminant validity were investigated, and confirmatory factor analyses were conducted for the complete BRFL as well as for a 10-item version excluding conditional items on child-related concerns. Furthermore, it was assessed how BRFL scores moderate the association between depression and suicide ideation. Results Results indicated an adequate fit of the data to the original factor structure. The total scale and the subscales of the German version of the BRFL had sufficient internal consistency, as well as good convergent and divergent validity. The BRFL demonstrated clinical utility by differentiating between participants with vs. without suicide ideation. Reasons for living proved to moderate the association between depression and suicide ideation. Conclusions Results provide preliminary evidence that the BRFL may be a reliable and valid measure of adaptive reasons for living that can be used in clinic and research settings.